Feeding strategies for Holando Argentino steers aimed at different markets - Zurbriggen, Gabriel Alberto; Kloster, Andrés María; Conde, María Belén; Grigioni, Gabriela; Latimori, Néstor Juan (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The objective was to evaluate the performance and meat quality of Holando Argentino (HA) steers under different feeding strategies. One hundred twenty-eight HA steers (181.4 ± 25.5 kg of live weight [LW]) were allocated to four treatments: FL: feedlot finishing during 98 days; Gr1.25: grazing with 1.25% LW/day maize grain supplementation during 235 days; Gr0.70: grazing with 0.70% LW/day maize grain supplementation during 331 days; and GrFL: 287 days grazing background and 116 days feedlot finishing. Average daily gains (ADG) were 1.14, 1.02, 0.82, and 0.81 kg/day for FL, Gr1.25, Gr0.70, and GrFL, respectively (p<0.01). Adjusted productivity ranged between 710 and 741 kg LW/ha (p>0.05). GrFL and Gr0.70 presented the highest carcass weight (CW; 288.3 ± 5.0 and 267.8 ± 12.2 kg, respectively, p<0.001). Gr0.70 presented the lowest longissimus thoracis (LT) L* (p<0.01) and the highest a* (p<0.05). Intramuscular fat was the highest for GrFL (4.86 ± 0.93%, p<0.05). In all strategies, LT shear force presented values of tender meat (29.9 ± 3.4 N, p=0.60). HA steers have the flexibility to produce tender meat under different, high-productivity strategies. Highlights: Holando Argentino steers produced tender meat under contrasting feeding strategies with high productivity. Intramuscular fat content was mainly determined by total grain intake. Grains can be used at different phases to manage live weight gains, as well as subcutaneous and intramuscular fat endpoints. Average daily gains, fat thickness, and carcass weight influenced meat color.